1977
DOI: 10.1007/bf00391917
|View full text |Cite
|
Sign up to set email alerts
|

An ultrastructural study of early endosperm development and synergid changes in unfertilized cotton ovules

Abstract: Excised, unfertilized cotton (Gossypium hirsutum L.) ovules were cultured for 1-5 days postanthesis and embryo-sac development was studied with the electron microscope. In some ovules the two polar nuclei fuse and the diploid endosperm nucleus goes through a limited number of free nuclear divisions after 2-3 days in culture. Each nucleus has two nucleoli, in contrast to nuclei of fertilized triploid endosperm which have three nucleoli. Precocious cell walls form between the endosperm nuclei on the 3rd day in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
1

Year Published

1977
1977
1998
1998

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 13 publications
2
25
1
Order By: Relevance
“…The tip of each of these walls grows in the absence of microtubules, similar to the growth seen in Stellaria (Newcomb and Fowke 1973) and Haemanthus (Newcomb 1978). But this is in contrast to reports of apical wall growth in the endosperm in the presence of microtubules in other soybean genotypes (Dute and Peterson 1992), wheat (Mares et al 1977), cotton (Jensen et al 1977), and Arabidopsis (Mansfield and Briarty 1990). We do not believe that our different results, when compared with other soybean genotypes, are a genotype-specific trait or that they resulted from poor tissue preparation, because microtubules were noted at other stages of endosperm development and in other tissues.…”
Section: Discussioncontrasting
confidence: 50%
“…The tip of each of these walls grows in the absence of microtubules, similar to the growth seen in Stellaria (Newcomb and Fowke 1973) and Haemanthus (Newcomb 1978). But this is in contrast to reports of apical wall growth in the endosperm in the presence of microtubules in other soybean genotypes (Dute and Peterson 1992), wheat (Mares et al 1977), cotton (Jensen et al 1977), and Arabidopsis (Mansfield and Briarty 1990). We do not believe that our different results, when compared with other soybean genotypes, are a genotype-specific trait or that they resulted from poor tissue preparation, because microtubules were noted at other stages of endosperm development and in other tissues.…”
Section: Discussioncontrasting
confidence: 50%
“…Tilton (1981) has proposed that the PT may release hormones after germination that cause the synthesis of both autolytic and chemotropic compounds in at least one synergid resulting in the degeneration of that synergid. This has been confirmed in vitro by the experiments of Jensen et al (1977). In our experiments, in which the style was cut off prior to the arrival of the PT in the ovary, no synergid degeneration occurred, suggesting that the degeneration of the synergid is triggered only after the PTs penetrate the ovary.…”
Section: Synergid Degenerationsupporting
confidence: 61%
“…F^rom evidence in Gossypium (Jensen, Schulz and Ashton, 1977), Proboscidea (Mogensen, 1978b) and Nicotiana (Mogensen and Suthar, 1979), it appears that pollen tube cytoplasm is in a degenerate state before a tube penetrates a synergid. Mogensen (1978b) suggested that the factor initiating this degeneration is of synergid origin whereas Haberlandt (1927) believed synergids secrete a substance which dissolves the end of pollen tubes.…”
Section: Discussion and Reviewmentioning
confidence: 99%